2019
DOI: 10.1080/16070658.2019.1641272
|View full text |Cite
|
Sign up to set email alerts
|

The impact of existing diabetes self-management education interventions on knowledge, attitudes and practices in public health care institutions in Harare, Zimbabwe

Abstract: Introduction: Diabetes self-management education (DSME) and medical nutrition therapy (MNT), provided by diabetes educators and registered dietitians respectively, considerably improve glycaemic control. However, it is unknown what interventions exist in many African countries and the impact thereof. Aim: To determine the impact of existing DSME interventions on knowledge, attitudes and practices (KAP) of adults with type 2 diabetes attending public health care facilities in Harare, Zimbabwe. Methods: A cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In Zimbabwe, dietitians and nutritionists need to fulfill 1200 clinical hours and be registered with the Allied Health Practitioners Council of Zimbabwe before they can practice in the clinical setting. Furthermore, they should constantly keep themselves updated with the latest developments in their field [10]. The New Zealand (NZ) Primary Healthcare Centres found similar barriers in the patients' management of DM even though NZ requires a dietitian to have specific qualification with varying degrees of experience and be registered with the Dietitians Board of NZ [11,18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Zimbabwe, dietitians and nutritionists need to fulfill 1200 clinical hours and be registered with the Allied Health Practitioners Council of Zimbabwe before they can practice in the clinical setting. Furthermore, they should constantly keep themselves updated with the latest developments in their field [10]. The New Zealand (NZ) Primary Healthcare Centres found similar barriers in the patients' management of DM even though NZ requires a dietitian to have specific qualification with varying degrees of experience and be registered with the Dietitians Board of NZ [11,18].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in 2019 reported that the number of T2DM patients that received nutrition education based on the attendance records from the previous year ranged from 4 to 19 at six selected clinics across nine health districts. The average number of T2DM patients seen by the diabetes educator were eight patients per week, or 32 cases per month [10]. The low number of patients could be related to the lack of interest of their preference to consult a doctor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations